2022
DOI: 10.1177/08862605221120909
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Sexual Abuse and Military Sexual Trauma Interact to Increase Suicide Risk: Results from a Nationally Representative Veteran Sample

Abstract: Childhood sexual abuse (CSA) and military sexual trauma (MST) are prevalent among veterans. Such exposures are associated with adverse mental-health sequelae, including elevated risk for suicidal thoughts and behaviors. Nonetheless, prior studies have largely focused upon discrete experiences of CSA or MST in circumscribed samples. In the current study, we analyzed data from a large, nationally representative sample of 4,069 US military veterans to examine main and interactive effects of CSA and MST in relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Female victims of SV commonly report at least one symptom of post-traumatic stress disorder [ 6 , 9 ]. Furthermore, experiencing child sexual abuse has been linked to various adverse psychosocial outcomes in adulthood, including substance misuse, decreased life satisfaction, and increased risk of suicidal behaviors [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Female victims of SV commonly report at least one symptom of post-traumatic stress disorder [ 6 , 9 ]. Furthermore, experiencing child sexual abuse has been linked to various adverse psychosocial outcomes in adulthood, including substance misuse, decreased life satisfaction, and increased risk of suicidal behaviors [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…MDPI and/or the editor(s) disclaim responsibility for any injury to people or property resulting from any ideas, methods, instructions, or products referred to in the content. 2 psychosocial outcomes in adulthood, including substance misuse, decreased life satisfaction, and increased risk of suicidal behaviors (Hailes et al, 2019;Holliday et al, 2023;Strizzi et al, 2022;).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the inclusion of those reporting harassment-only MST may alter the strength of these associations, perhaps accounting for the null results observed in two of the three studies. The significant results documented by Holliday et al (2023) might be attributed to their nationally representative sample, as both Baca et al (2023) and Blais et al (2022) used convenience samples with a smaller size. The current study addressed these possibilities by assessing revictimization in only those who report MST that involved assault or attempted assault.…”
mentioning
confidence: 97%
“…Blais et al (2022) and Baca et al (2023) reported that there was no significant difference between MST and revictimization (i.e., a history of both MST and premilitary victimization) on suicidal risk. However, Holliday et al (2023) demonstrated that among MST survivors, those who experienced childhood sexual abuse reported higher suicide risk. All three studies mentioned above included harassment-only exposures, which are associated with a lower risk for psychological distress and suicide risk (Blais & Geiser, 2019; Millegan et al, 2015; Street et al, 2008).…”
mentioning
confidence: 98%